Skrining Fitokimia Metabolit Sekunder pada Daun Binahong (Anredera cordifolia (Ten.) Steenis) untuk Uji In Vitro Daya Hambat Pertumbuhan Aeromonas hydrophila - Prita Yulianti Anasta br G; Mohammad Basyuni; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2013)
Binahong leaves are one of natural product to be used to treat the diseaseof living organisme due to having secondary metabolite to show antibacterialactivity. The purpose of this research was to study secondary metabolite ofBinahong leaves of which showing antibacterial, to analysis effectivity ofantibacterial Binahong leaves extract to inhibit growth of bacteria Aeromonashydrophila. An experimental laboratory with six treatments and three replicationsfor in vitro was tested. A paper disc soaked in a solution of Binahong leavesextract was used for in vitro at a concentration of 0% (w/v); 0,2%; 0,4%; 0,6%;0,8%; positive control (Oxytetracycline). In vitro test showed that Binahongleaves extract inhibited the growth of bacteria A. hydrophila with a inhibitionarea around the paper disc. Diameter Inhibition area that formed was 0 mm ( 0 %negative control ), 8.4 mm (0.2 %), 9.4 mm (0.4 %), 10.5 mm (0.6 % ) ; 11 , 9 mm(0.8 % ), 27.5 mm (positive control). The increase concentration of Binahongleaves extract enhanced the growth inhibition area. Phytochemical screening ofBinahong leaves extract showed that the extracts contained flavonoid, phenol,saponin, alkaloid, steroid/triterpenoid.Keywords : Binahong leaves, Aeromonas hydrophila, flavonoid, phenol, saponin,alkaloid, triterpenoid, β –sitosterol